Factors predictive of parametrial boost in patients with cervical cancer treated with definitive chemoradiation - Kurl E. Jamora; Johanna Patricia A. Cañal (Elsevier, 2022)
Objective: The aim of this study is to identify demographic, clinical, and treatment-related characteristics associated with the prescription of parametrial boost (PMB) in cervical cancer patients undergoing definitive chemoradiation. Materials/Methods: A retrospective chart review of 132 non-metastatic cervical cancer patients treated with definitive chemoradiation from May 2017 to December 2019 was performed. Demographic, clinical, and treatment characteristics were obtained and compared between those who received PMB and those who did not. Clinical outcomes (pelvic recurrence, tumor persistence, distant metastases, and median survival time) were also gathered and compared. Statistical software was used for analysis, with a p < 0.05 considered statistically significant. Results: Of the 132 patients included in the analysis, 74 (56%) received PMB of 10 Gy in five daily fractions and 58 (44%) did not. Patients who received PMB were more likely to have pelvic sidewall invasion at the time of diagnosis (OR 4.053, 95% CI 1.163-14.13, p < 0.05) and received more cycles of concurrent chemotherapy during whole pelvis irradiation (OR 2.149, 95% CI 1.370-3.371, p < 0.05). At a median follow-up of 24 months, there was no statistically significant difference in the crude rates of pelvic recurrence, tumor persistence, distant metastasis, and median survival between the two groups. Conclusion: Presence of pelvic sidewall invasion at diagnosis and increased number of chemotherapy cycles were predictive of administering PMB after whole pelvis irradiation. There was no significant difference in treatment outcomes for those with and without PMB.